Epidemiology of malaria in children living at Igbo-Ora, South Western Nigeria (2008)
Malaria transmission is seasonal with higher transmission occurring in the rainy season. The burden of malaria falls mainly on children and causes anaemia and fever. Children of school going age are affected and this leads to absence from school. Blood samples were collected from children aged 10 days to 15 years in dry and rainy seasons. Parasite densities were determined by microscopy. Malaria prevalence was higher in the rainy season than in the dry season. In the dry season, 42.4% of the children studied were positive for P. falciparum. While at the end of the rainy season 48.4% of the children were malaria positive. The parasite prevalence was not significantly different between males and females. Parasite densities varied from 18 to 52174 parasites per 111 of blood. The most abundant group ranged from 1-100 (59%). There was a significant correlation between parasite density and age with the mean parasite density decreasing with age group. The study shows that malaria is more prevalent in the rainy season, and children in rural areas have high prevalence of asymptomatic parasitemia which might lead to symptomatic malaria. The results show that malaria immunity increases with age in both seasons.